Learners’ personal narratives on their way to EFL competence: The impact of teachers on learners’ development - Siek-Piskozub, Teresa; Jankowska, Aleksandra (Glottodidactica, 2018)
In this paper, the authors present an analysis of students’ narratives on their way to becoming competent English as a foreign language (EFL) users. Before presenting our study we refer to the ecological perspective on language learning/teaching, which may show the important impact of the learners’ environment for EFL development. We refer to studies which point to the importance of the environment for language learning and which used various methods of research. In our study, we apply a narrative approach. The collected corpus of narratives is analysed following the grounded theory within the psychological model of wellbeing, i.e. the PERMA model. Eventually, we decided to concentrate on the impact teachers have on learners’ emotions, engagement, meaning, relationships and accomplishment.